2014
DOI: 10.5812/jjm.12287
|View full text |Cite
|
Sign up to set email alerts
|

Post Neurosurgical Meningitis due to Colistin Heteroresistant Acinetobacter baumannii

Abstract: Introduction:Recently Acinetobacter baumannii isolates have emerged as a problematic infectious agent that causes meningitis in neurosurgical patients. Colistin has been used successfully for the treatment of A. baumannii meningitis but colistin resistant isolates have been reported worldwide.Case Presentation:Two isolates of A. baumannii were cultured during a five-day period from cerebrospinal fluid (CSF) samples of a 20-year-old man with a gunshot trauma in the abdomen, which had exited from his back. Antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
(34 reference statements)
1
12
0
4
Order By: Relevance
“…A similar phenotype has also been described in clinical isolates of Stenotrophomonas maltophilia [29] and carbapenem-resistant A. baumannii [30]. Curiously, this phenomenon has enhanced colistin resistance in A. baumannii [31], an issue that is now of great interest, since colistin is the drug of choice for A. baumannii therapy [32][33][34] To answer the question of whether this phenotypic manifestation has a genetic basis, further investigation is required, including genomic sequencing. Choi and Ko stated that the two-component gene system PmrA/B is associated with the emergence of colistin heteroresistance in A.baumannii [35].…”
Section: Discussionmentioning
confidence: 65%
“…A similar phenotype has also been described in clinical isolates of Stenotrophomonas maltophilia [29] and carbapenem-resistant A. baumannii [30]. Curiously, this phenomenon has enhanced colistin resistance in A. baumannii [31], an issue that is now of great interest, since colistin is the drug of choice for A. baumannii therapy [32][33][34] To answer the question of whether this phenotypic manifestation has a genetic basis, further investigation is required, including genomic sequencing. Choi and Ko stated that the two-component gene system PmrA/B is associated with the emergence of colistin heteroresistance in A.baumannii [35].…”
Section: Discussionmentioning
confidence: 65%
“…Later, in their studies in Argentine, Rodriguez et al [19] Rodriguez et al [20] have found 46% and 43% heteroresistance rates in 2009 and 2010, respectively. In their case report, Moosavian et al [10] have recently demonstrated post neurosurgical meningitis due to colistin heteroresistant A. baumannii. They have also reported the generation of colistin resistant A. baumannii from colistin susceptible-heteroresistant strains during colistin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Heteroresistance to carbapenems has been reported in A. baumannii, and it is believed to be the cause of increasing CR A. baumannii in Greece [1,9] . Recently, Moosavian et al [10] have reported a case of meningitis due to colistin heteroresistant A. baumannii and observed colistin resistance development during treatment with colistin.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies from clinical settings throughout the world have indicated the emergence of colistin-resistant AB as an important healthcare problem [10,14]. Colistin-susceptible AB strains can easily transform into colistin-resistant or heteroresistant clones, or colistin heteroresistant strains can transform into colistin-resistant clones via exposure to colistin [15][16][17][18]. In 2016, the emergence of plasmid-mediated colistin resistance in an E. coli strain by the MCR-1 mechanism was reported from China, which made scientists focus on the urgent need for global action in the fight against pan-drug-resistant Gram-negative bacteria [19].…”
Section: Introductionmentioning
confidence: 99%